Identification of potential target genes of breast cancer in response to Chidamide treatment - Han, Han; Feng, Xue; Guo, Yarui; Cheng, Meijia; Cui, Zhengguo; Guo, Shanchun; Zhou, Weiqiang (Frontiers in Molecular Biosciences, 2022)
Chidamide, a new chemically structured HDACi-like drug, has been shown to inhibit breast cancer, but its specific mechanism has not been fully elucidated. In this paper, we selected ER-positive breast cancer MCF-7 cells and used RNA-seq technique to analyze the gene expression differences of Chidamide-treated breast cancer cells to identify the drug targets of Chidamide's anti-breast cancer effect and to lay the foundation for the development of new drugs for breast cancer treatment. The results showed that the MCF-7 CHID group expressed 320 up-regulated genes and 222 down-regulated genes compared to the control group; GO functional enrichment analysis showed that most genes were enriched to biological processes. Subsequently, 10 hub genes for Chidamide treatment of breast cancer were identified based on high scores using CytoHubba, a plug-in for Cytoscape: TP53, JUN, CAD, ACLY, IL-6, PPARG, THBS1, CXCL8, IMPDH2, and YARS. Finally, a combination of the GEPIA database and Kaplan Meier mapper to compare the expression and survival analysis of these 10 hub genes, TP53, ACLY, PPARG and JUN were found to be potential candidate genes significantly associated with Chidamide for breast cancer treatment. Therefore, we identified 4 hub genes for Chidamide treatment of breast cancer by bioinformatics analysis, providing a more theoretical basis for Chidamide treatment of breast cancer at the molecular level.